Marketplace Lending and Fintech: The States Object - Savoie, Robert; Hoffman, Philip (PJ) (The Business Lawyer, 2018)
Fintech Charter Developments Special Purpose National Bank Charter for Fintech Lenders The OCC released its proposal for a special purpose national bank ("SPNB") charter for fintech companies in December 20163 As part of that proposal, the OCC issued a white paper that sets forth the basis for its authority to grant special purpose charters for national banks under the National Bank Act, and it requested comments.4 The OCC viewed the provision of financial services through fintech as merely an extension of its existing chartering authority.5 The white paper explains that companies that hold fintech charters will be subject to the same laws, regulations, examination, reporting requirements, and ongoing supervision as other national banks.6 SPNBs would generally be subject to the prohibitions on engaging in unfair, abusive, and deceptive acts or practices under the Federal Trade Commission Act and the Consumer Financial Protection Act.7 The white paper includes a detailed treatment of state law preemption, but notes that state law would apply, or in some circumstances, would not apply to an SPNB in the same way and to the same extent that state law applies to a full-service national bank.8 It must be noted that an SPNB would be able to export its home state's interest rate nationwide, and it would be exempt from state licensing laws, such as those regulating money transmitters.9 According to the white paper, SPNBs may engage only in activities that are permissible for a national bank and must limit their activities to fiduciary activities and activities within the business of banking.10 As such, an SPNB that conducts activities other than fiduciary activities must conduct at least one of the following three core banking functions: receiving deposits, paying checks, or lending money.11 National banks are required to meet very high supervisory standards and SPNBs will be no exception. "16 By not allowing SPNBs to take deposits, fintech charter applicants would not be required to seek approval from the Federal Deposit Insurance Corporation ("FDIC") as part of the application process.17 Additionally, without taking insured deposits, fintech companies would not fall under the definition of "bank" in the Bank Holding Company Act,18 so that owners or controllers of an SPNB would not be subject to oversight by the Federal Reserve Board and would avoid being subject to significant regulatory restrictions on their business activities.19 The regulations that implement the Community Reinvestment Act ("CRA") are also triggered by a bank's acceptance of insured deposits.20 While an SPNB would not have to follow those requirements, the Supplement would require "all SPNBs engaged in lending or providing financial services to consumers or small businesses" to commit to the implementation of a financial inclusion plan by entering into an operating agreement with the OCC.21 Applicants for fintech charters would be required to publish financial inclusion plans for public comment during the application process that would be used by the OCC throughout supervision and examination, mirroring the factors that the prudential regulatory agencies consider in performing CRA exams.22 Essentially, the Supplement proposes that an SPNB holding a fintech charter adhere to substantially similar supervisory expectations for community reinvestment that apply under the CRA to national banks that accept FDIC-insured deposits, albeit through a different mechanism. [...]the Vermont amendments appear to require licensure by marketplace lenders and other companies engaged in activities where they facilitate the origination of consumer loans for consumers. Id. at 14-17. [...]the OCC would render inapplicable to any SPNB certain state-imposed licensing fees that defray the operating expenses of the NYDFS.